Anabolic and Pro-metabolic Functions of CREB-CRTC in Skeletal Muscle: Advantages and Obstacles for Type 2 Diabetes and Cancer Cachexia - Berdeaux, Rebecca; Hutchins, Chase (Frontiers in Endocrinology, 2019)
cAMP is one of the earliest described mediators of hormone action in response to physiologic stress that allows acute stress responses and adaptation in every tissue. The classic role of cAMP signaling in metabolic tissues is to regulate nutrient partitioning. In response to acute stress, such as epinephrine released during strenuous exercise or fasting, intramuscular cAMP liberates glucose from glycogen and fatty acids from triglycerides. In the long-term, activation of Gs-coupled GPCRs stimulates muscle growth (hypertrophy) and metabolic adaptation through multiple pathways that culminate in a net increase of protein synthesis, mitochondrial biogenesis, and improved metabolic efficiency. This review focuses on regulation, function and transcriptional targets of CREB (cAMP response element binding protein) and CRTCs (CREB regulated transcriptional coactivators) in skeletal muscle and the potential for targeting this pathway to sustain muscle mass and metabolic function in type 2 diabetes and cancer. Although the muscle-autonomous roles of these proteins might render them excellent targets for both conditions, pharmacologic targeting must be approached with caution. Gain of CREB-CRTC function is associated with excess liver glucose output in type 2 diabetes, and growing evidence implicates CREB-CRTC activation in proliferation and invasion of different types of cancer cells. We conclude that deeper investigation to identify skeletal muscle specific regulatory mechanisms that govern CREB-CRTC transcriptional activity is needed to safely take advantage of their potent effects to invigorate skeletal muscle to potentially improve health in people with type 2 diabetes and cancer.